One Step Ultrasonic Assisted Sol-Gel Synthesis of Silica Based Aerogel From Gold Mine Waste: The Effect of Synthesis Parameters on the Structure - Mermer, Nevin Karamahmut; Piskin, Sabriye (CHEM SOC PAKISTAN, 2018)
The synthesis of silica based hydrophobic aerogel from gold mine waste is an interesting direction on usage of mine waste due to the chemical composition (Si, Al). An attempt was made in the present work to obtain the silica based hydrophobic aerogel from gold mine waste and investigation of the effect of parameters in the synthesis. One step ultrasonic assisted sol-gel method was used for the synthesis. Mine waste is chemically analysed and used in the synthesis. Density and contact angle measurements, FT-IR (Fourier-Transform Infrared Spectroscopy), XRD (X-ray Diffraction), XRF (X-ray Fluorescence), SEM (Scanning Electron Microscope) and N-2 adsorption/desorption devices were used in the current work. The effects of the synthesis parameters such as pH, Si /total material mass ratio, reflux time and temperature, aging time andtemperature and drying method on the structure of material were examined. The obtained optimum samples were used in the production of thermal insulating plaster. Different mass percentages of aerogel were mixed to the plaster mortar (1, 5 and 10 %). Thermal conductivities of plaster samples were investigated. Studies have shown that the gold mine waste is a suitable silicon source for the synthesis of silica based hydrophobic aerogel via ambient pressure. Aerogel containing plaster can be used for insulation purposes in constructions.
Keywords: Aerogel; Waste; Hydrophobicity; Density; Thermal insulating plaster; AMBIENT-PRESSURE; PHYSICOCHEMICAL PROPERTIES; SURFACE MODIFICATION; MESOPOROUS SILICA; TAILINGS; REMOVAL; PRODUCTS; POWDERS; METALS; WATER; Chemistry